ANALISIS KINERJA SIMPANG EMPAT BERSINYAL PEREMPATAN PASAR MAYONG JEPARA MENGGUNAKAN METODE MKJI 1997 DAN WEBSTER - Umam, Khotibul; Ahmad , Arrisal Khoirudin; Saputro, ST., MT., Yayan Adi; Qomaruddin, Mochammad; Faqih, Nasyiin (Jurnal Konstruksi dan Infrastruktur : Teknik Sipil dan Perencanaan, 2024)
Congestion is caused by the increasing number of vehicles, however. Not matched by the increase in supporting transportation facilities. Jepara Regency is located in the province of Central Java, with an area of 1,004 km2. At Simpang Empat Mayong around the intersection there are shopping areas and educational institutions, this factor causes the high number of passing vehicles. In this study, researchers used the 1997 MKJI method and the Webster method. The peak flow occurs on Tuesday at 15.30-16.30 with vehicles 2920.5 pcu/hour. Side resistance on each approach is low. Jalan Mayong-Welahan peak traffic flow was 349.6 pcu/hour, Jalan Jepara-Kudus (B) was 811.1 pcu/hour, Jalan Mayong-Pancur was 301.7 pcu/hour and Jepara-Kudus (D) was 1133.5 pcu/hour. Degree of saturation on Mayong-Welahan road 1.28 pcu/hour and 82 seconds delay, Jepara-Kudus (B) road 1.30 pcu/hour 120 second delay, Mayong-Pancur road 1.29 pcu/hours with 98 second delay and Jepara-Kudus (D) degree of vehicle saturation is 1.29 pcu/hour with a delay of 98 seconds. The level of service is jammed. increase that was initially Stalled (E). MKJI method signal time andWebster 120 seconds, green time for Jalan Mayong-Welahan MKJI 17 seconds, Webster 14 seconds, Jalan Jepara-Kudus (B) MKJI andWebster 35 seconds, Jalan Mayong-Pancur MKJI 14, Webster 12, Jalan Jepara-Kudus (D) MKJI 38 and Webster 41 sec. Keyword: intersection, traffic, MKJI, Webster